2019
DOI: 10.1186/s12890-019-0943-2
|View full text |Cite
|
Sign up to set email alerts
|

Demographic and clinical predictors of progression and mortality in connective tissue disease-associated interstitial lung disease: a retrospective cohort study

Abstract: BackgroundConnective tissue disease-associated interstitial lung disease (CTD-ILD) is associated with reduced quality of life and poor prognosis. Prior studies have not identified a consistent combination of variables that accurately predict prognosis in CTD-ILD. The objective of this study was to identify baseline demographic and clinical characteristics that are associated with progression and mortality in CTD-ILD.MethodsPatients were retrospectively identified from an adult CTD-ILD clinic. The predictive si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
29
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(37 citation statements)
references
References 41 publications
(59 reference statements)
3
29
1
Order By: Relevance
“…The commonly reported PFT parameters that are associated with ILD prognosis include FVC and DLco. [ 4 5 6 ] Nathan et al . [ 4 ] reported that the median survival among IPF patients with baseline FVC percent predicted <55% was 27.4 months and among those with DLco percent predicted <35% was 31.3 months compared to 55.6 months for FVC >70% and 67.3 months for DLco >50%.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The commonly reported PFT parameters that are associated with ILD prognosis include FVC and DLco. [ 4 5 6 ] Nathan et al . [ 4 ] reported that the median survival among IPF patients with baseline FVC percent predicted <55% was 27.4 months and among those with DLco percent predicted <35% was 31.3 months compared to 55.6 months for FVC >70% and 67.3 months for DLco >50%.…”
Section: Discussionmentioning
confidence: 99%
“…[ 1 2 3 ] Studies in ILD have identified important physiological prognostic markers associated with reduced survival, such as forced vital capacity (FVC), total lung capacity (TLC), diffusion capacity of the lung for carbon monoxide (DLco), 6-min walk distance (6MWD), and desaturation during the 6-min walk test (6MWT). [ 4 5 6 7 8 ] However, the cited studies did not specify what proportions of these patients have underlying pulmonary hypertension (PH). Estimates suggest that the prevalence of PH among ILD patients ranges between 30% and 74% depending on the ILD subtype and studied population.…”
mentioning
confidence: 99%
“…These differences may be attributable to the different genetic and ethnic backgrounds of the study subjects and also to the heterogeneity of the non-IPF patients in the above publications [5,7,11]. There are also some previous studies suggesting that ethnic background might influence the clinical features and disease course of the ILD patients [21,22]. AE-ILD has been reported to be the most common individual cause for a respiratory deterioration in different types of ILDs accounting for 29-55% [5,6,10,11] of respiratory hospitalizations, values consistent with our own findings.…”
Section: Plos Onementioning
confidence: 93%
“…CT presented in table [2]. The pleural line was thick in 24%, smooth in 46.0% and irregular in 30.0%.…”
Section: Results Of Chest Ultrasound and High Resolutionmentioning
confidence: 95%
“…ILD is not a single disease, but it includes a group of disorders that are characterized by varying combinations of inflammation and fibrosis may be idiopathic or caused by exposure to organic and inorganic substances [i.e pneumonitis and pneumoconiosis], medical conditions [i.e., connective tissue diseases [CTDs], multisystem diseases, drugs, infection and radiation therapy [2].…”
Section: Introductionmentioning
confidence: 99%